Afrostilobezzia, a new genus of predatory biting midges from the Afrotropical Region (Diptera: Ceratopogonidae) - Szadziewski, Ryszard; Dominiak, Patrycja (Zootaxa, 2015)
A new genus Afrostilobezzia gen. nov. including A. clastrieri sp. nov. and A. ornatithorax (Clastrier, 1988) comb. nov. is described from West Africa (Nigeria and Guinea).